The Boma: Keeping livestock cool during a climate crisis - International Livestock Research Institute (International Livestock Research Institute, 2021)
There's a growing problem across the world, one that could make keeping livestock outdoors almost impossible in just a few decades, and jeopardize the health and livelihoods of hundreds of millions of people. That problem is heat stress, caused by rising temperatures and global warming. It's a serious problem which is already affecting livestock health and welfare, particularly in outdoor farming, and subtropical or tropical zones. In the last episode of this season, presenters Brenda Coromina and Elliot Carleton hear from Philip Thornton, ILRI scientist and one of the top 50 most influential climate scientists worldwide. He warns about the consequences of living in a world where two-thirds of all cattle could be at risk of heat stress, along with many other livestock species. What options are there for mitigation and adaptation? And whose responsibility will it be to avert disaster? Listen to The Boma to find out!